Performance and emission characteristics evaluation of CRDI engine using alternate fuel. (2021) - Yogaraj, D.; Ragothaman, G.; Devaraj, A.; Udhayakumar, K.
Abstract: The experimental study is performed on the performances and emission characteristics of Common Rail (CRI) injection C.I engine. A 4-stroke engine, a cylinder, and a 3.5 kW water-cooled engine were used for the experiment. B10, B20 and B30 biodiesel blends was used to perform performances and emission test under different loading conditions. Several parameters were recorded, such as the BSFC, BTE, the emission of carbon monoxide, hydrocarbons, smoke and oxides of nitrogen in the exhaust. The major properties of Karanja's methyl esters were compared to diesel fuel. The performances and exhaust emissions was compared to single diesel, using karanja fuel blends. This combination shows a significant improvement for the exhaust emission and the fuel consumption under varying loading conditions.